Immunomodulatory features of MSC-derived exosomes decorated with DC-specific aptamer for improving sublingual immunotherapy in allergic mouse model - Mahvash Sadeghi; Sajad Dehnavi; Ali Khodadadi; Ata. A. Ghadiri; Ali Ganji; Moosa Sharifat; Ali Asadirad (Stem Cell Research & Therapy)
Abstract Introduction Sublingual immunotherapy (SLIT) is an effective and injection-free route for allergen-specific immunotherapy (AIT). Mesenchymal stromal/stem cell (MSC)-derived exosomes (Exo) has been identified as a novel delivery platform with immunomodulatory capacities. In addition, targeting agents such as aptamers (Apt) have been extensively used for specific delivery approaches such as direct delivery of allergen formulations to dendritic cells (DC) to improve the efficacy of specific immunotherapy. In this study, we assessed the effects of MSC-derived Exos containing ovalbumin (Ova) which decorated with DC-specific aptamer in allergic rhinitis mice model. Materials and methods Exos were harvested from adipose tissue-derived MSCs, and Exo-Apt-Ova complex was formulated. Then, Ova-induced allergic asthma model was simulated and sensitized BALB/c mice were treated sublingually with Exo-Apt-Ova complex (5 µg Ova) twice weekly for 8 weeks. Ova-specific IgE levels in serum and concentrations of interferon-gamma (IFN-γ), interleukin (IL)-4, and transforming growth factor-beta (TGF-β) in the supernatant of cultured splenocytes were evaluated using enzyme-linked immunosorbent assay (ELISA). In addition, lung histologic analysis and nasopharyngeal lavage fluid (NALF) cell count were performed. Results Administration of Ova-incorporated Apt-modified Exos dramatically increased IFN-γ and TGF-β levels, and decreased IL-4 and IgE levels. In addition, inflammatory responses in the lung tissue and the number of eosinophils in NALF decreased. Conclusion SLIT using Exo-Ova (5 µg) decorated with DC-specific aptamer induced immunomodulatory responses and remarkably attenuated allergic airway inflammation in mice.